Evaluation of in vitro culture media of adult Brugia malayi with glucose supp/ementetipn - Sri Sumarni Sri Sumarni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: The circulating antigen of filariasis malayi patient is the excretory/secretory (ES) protein. It was used as antigen in monoclonal antibody production. The ES protein can be obtained by in vitro culture of filarial worm Brugia malayi.Objective : The aims of this research was to evaluate in vitro culture media with glucose supplementation of adults B.malayi to obtain the ES protein maximally.Methods: Adult males and females B.malayi were cultivated in vitro in medium with glucose supplementation in different concentrations (1%, 3% and 5%). The culture media were changed daily and analysis of its protein were carried out quantitatively using Bradford method, and gel electrophoresis (SDS PAGE) for qualitative protein analysis. The cuticle of adults B.malayi were extracted by detergent cetyltrimethyl ammonium bromide (CTAB).Results: The effective culture medium was RPMI with 1% glucose supplementation to produce ES protein maximally, and longevity of worms could survive for 6 days. The quantitative protein concentration of female worms culture medium was 0.2-1.85 ug/ml, and the protein molecular weight of female worms cuticle was 26 kDa- 116 kDa. The protein concentration of male culture medium was 0.2-0.5 ug/ml, the molecular weight of adult male cuticle protein was 34 kDa- 56kDa. The peak concentration of protein in both cultivation was observed on the third day.Conclusion: The best medium for in vitro cultivation of adults B.malayi was RPMI with 1% glucose supplementation. The protein concentration of the female culture media was higher than male .Key words: glucose supplementaion - in vitro culture - filarial worms -Brugia malayi - ES protein